What is Islamic Economics? An Attempt to Classify the Definitions of Islamic Economics - Ujang Syahrul Mubarrok; Izzani Ulfi; Muhammad Akbar Izzulhaq (Universitas Muhammadiyah Sidoarjo, 2022)
Various definitions of Islamic economics have been offered by academics and scholars according to their respective perspectives and backgrounds. Those perspectives and backgrounds resulting numerous definitions of Islamic economics which make it difficult for students and novice readers to understand Islamic economics. Therefore, it is necessary to identify and classify the definition of Islamic economics into several groups. This study attempted to classify the existing definitions of Islamic economics based on the important themes contained in the definition. This study classifies the definitions of Islamic economics using a literature review, with the help of NVivo software. The stages of data analysis in this study is reading all definitions to identify several key points to assign to the group the definition of Islamic economics as a scientific discipline or not; identify the important points of the definition included in the defined group of Islamic economics as a discipline; and presenting the identification resultsThere are four groups in defining Islamic economics, namely Islamic economics as a dogma or doctrine, Islamic economics as an economic system, Islamic economics as the economy of Muslim countries, and Islamic economics as a scientific discipline. The classification of the definition of Islamic economics is critical to make it easier for any readers to have a better understanding of the definition of Islamic economics.